Thermophysical, diffusion, and segregation processes in the frictional contact zone - Igor V Kolesnikov (Advanced Engineering Research, 2015)
The calculation of the temperature field for the tribosystem of wheel - composition brake shoe of the rolling stock has shown that the maximum temperature in the wheel is not on the surface, but at 200-1000 micron distance from the friction surface. Under friction, as a result of the thermomechanical destruction of the polymer shoe there evolves hydrogen that is absorbed by the contact surface of the wheel. At that, the maximum hydrogen concentration coincides with the maximum temperature. The research results of the segregation phenomena of alloying and impurity elements in the iron grain boundaries are presented. It is shown that the consistency of the rates of the transfer film formation and its destruction is the kinetic condition of self-organization on the antifriction tribo-contact. The atomic-binding energy of different elements to the grain surface is a periodic function of the atomic numbers of the elements. This may serve as a theoretical basis for predicting the strength properties of steel with a different composition of alloying and impurity elements. The obtained results indicate the promising application of XPS and AES of quantum chemistry in solving tribological tasks.